Empowering activists or autocrats? The Internet in authoritarian regimes. (May 2015) - Rød, Espen Geelmuyden; Weidmann, Nils B
The reported role of social media in recent popular uprisings against Arab autocrats has fueled the notion of 'liberation technology', namely that information and communication technology (ICT) facilitates organization of antigovernment movements in autocracies. Less optimistic observers, on the other hand, contend that ICT is a tool of repression in the hands of autocrats, imposing further restrictions on political and social liberties. We investigate whether the liberation- or the repression-technology perspective can better explain empirically observed patterns. To this end, we analyze two outcomes. First, we look at which autocracies are more likely to adopt and expand the Internet. In line with the repression technology expectation, we find that regimes aiming to prevent any independent public sphere are more likely to introduce the Internet. Second, we study the effects of the Internet on changes towards democracy. This analysis reveals no effect of the Internet on political institutions. These findings provide moderate support for the 'repression technology' perspective, and suggest that the Internet has not – at least in its first two decades of existence – contributed to a global shift towards democracy.